ay + 2by + Ac + 2bx
Me ajudem, Agradeço !❤️
Soluções para a tarefa
Respondido por
0
Fatorando!
ay + 2by + ax + 2bx =
y . (a + 2b) + x . (a + 2b) =
(y + x) . (a + 2b) {resultado final > forma fatorada}
ay + 2by + ax + 2bx =
y . (a + 2b) + x . (a + 2b) =
(y + x) . (a + 2b) {resultado final > forma fatorada}
Perguntas interessantes
Matemática,
11 meses atrás
História,
11 meses atrás
Inglês,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Direito,
1 ano atrás
Artes,
1 ano atrás
Português,
1 ano atrás